2019
DOI: 10.1021/acs.nanolett.9b02646
|View full text |Cite
|
Sign up to set email alerts
|

Spherical Nanovesicles Transform into a Multitude of Nonspherical Shapes

Abstract: Nanovesicles are closed, bubblelike surfaces with a diameter between 20 and 200 nm, formed by lipid bilayers and biomembranes. Electron microscopy (EM) studies have shown that these vesicles can attain both spherical and nonspherical shapes. One disadvantage of EM methods is that they provide only a single snapshot of each vesicle. Here, we use molecular dynamics simulations to monitor the morphological transformations of individual nanovesicles. We start with the assembly of spherical vesicles that enclose a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
85
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(89 citation statements)
references
References 43 publications
4
85
0
Order By: Relevance
“…These shape transformations of nanovesicles are, however, accessible to molecular dynamics simulations. [ 16,17,41–45 ] Here, we focus on two recent simulations [ 16,17 ] which revealed that the leaflet tensions and the concentrations of small solutes, which adsorb onto the membranes, represent important control parameters for the nanovesicle morphologies, see Figure 7 and Section 7.3 further below. In particular, these studies identified parameter values for the formation of membrane necks.…”
Section: Remodeling Of Membrane Shapementioning
confidence: 99%
See 3 more Smart Citations
“…These shape transformations of nanovesicles are, however, accessible to molecular dynamics simulations. [ 16,17,41–45 ] Here, we focus on two recent simulations [ 16,17 ] which revealed that the leaflet tensions and the concentrations of small solutes, which adsorb onto the membranes, represent important control parameters for the nanovesicle morphologies, see Figure 7 and Section 7.3 further below. In particular, these studies identified parameter values for the formation of membrane necks.…”
Section: Remodeling Of Membrane Shapementioning
confidence: 99%
“…Budding of nanovesicles as observed in molecular dynamics simulations. [ 16 ] Each snapshot displays half a vesicle, with the cross‐section across the hydrophobic core of the bilayer membrane in grey and the lipid head groups in green. The budding transformations were induced by decreasing the volume v of the two spherical vesicles with v = 1.…”
Section: Remodeling Of Membrane Shapementioning
confidence: 99%
See 2 more Smart Citations
“…Notably, when the volume of spherical vesicles is experimentally reduced, mimicking osmotic deflation, the vesicles undergo greatly differing shape transformations. This polymorphism is due to the redistribution of a small fraction of the lipids between the inner and outer leaflets of the bilayered membranes thereby, reduce the overall bilayer tension and, produce tensionless bilayers (Ghosh et al, 2019).…”
Section: Osmotic Pressure Desiccation and Hydrationmentioning
confidence: 99%